Implementation of the Inter-Agency Collaboration in Vocational Education of Students with Learning Disabilities towards Preparation of Career Experience: A Qualitative Approach - Abdullah, Noraini; Yasin, Mohd Hanafi Mohd (Modern Perspectives in Language, Literature and Education Vol. 5, 2021)
Inter-agency coordination is critical to the advancement of technical education services for students with special needs, including those with learning difficulties. Inter-agency partnership is a group of teachers, guardians, school representatives, and representatives from outside organizations that work together to execute, coordinate, and create programmes for students. However, the implementation of inter-agency collaboration with schools has remained at low levels. Therefore, this study was undertaken to explore the implementation of inter-agency collaboration and the obstacles faced by teachers in vocational education of students with learning disabilities towards career experience preparation. This study used a qualitative approach with case study design. Data were collected using interviews involving 10 teachers from vocational education in 6 Integration Program with Learning Disabilities (IPLD) schools. The findings show that there is inter-agency collaboration implemented with the schools involved but the implementation is not comprehensive. Results from interviews show that there are several obstacles in the implementation of inter-agency collaboration in terms of student attitude, parental attitude, and attitude of employers, financial problems and lack of information about the implementation of vocational education in IPLD. This study is expected to assist schools in implementing inter-agency collaboration to provide the best service to enhance the skills and careers of students with special needs especially students with learning disabilities. Moreover, teachers should work to establish a collaboration with various parties such as a joint venture especially in the field of vocational education, to get advice and work to highlight the existing potentials in students with learning disabilities.